Pengaruh Gaya Belajar Terhadap Prestasi Belajar Peserta Didik Kelas VII di SMP Negeri Halioan Tahun Ajaran 2023/2024 - Sisilia Seuk; Wolfgang Asindo Seran; Stefania Sonia Manek; Ivony Sarlin Asa (Lembag, 2024)
The purpose of this research: (1) to analyze the influence of student learning styles on the learning achievement of class VII students at Halioan State Middle School. (2) determine learning styles on the learning achievement of class VII students at Halioan State Middle School. The method used is a quantitative method. The research results showed that 35.2% of students had a visual learning style, 55.2% of students had an auditory learning style, and 29.6% of students had a kinesthetic learning style. In general, students tend to have visual and auditory learning styles. The results of hypothesis testing show that learning style has a relationship with learning achievement. Learning style has a significant effect on learning achievement. Learning style has a contribution or influence of 52% on student learning achievement and the remaining 48% is influenced by other variables that are not analyzed in the model.